Magnetization profile of magnetic impurities in graphene nanoribbons - Ferreira, Mauro; Power, Stephen (My University, 2011)
The magnetic properties of graphene-related materials, and in particular, the spin-polarized edge states predicted for pristine graphene nanoribbons (GNRs) with certain edge geometries have received much attention recently due to a range of possible technological applications. However, the magnetic properties of pristine GNRs are not predicted to be particularly robust in the presence of edge disorder. In this work, we examine the magnetic properties of GNRs doped with transition-metal atoms using a combination of mean-field Hubbard and density functional theory techniques. The effect of impurity location on the magnetic moment of such dopants in GNRs is investigated for the two principal GNR edge geometries: armchair and zigzag. Moment profiles are calculated across the width of the ribbon for both substitutional and adsorbed impurities, and regular features are observed for zigzag-edged GNRs, in particular. Unlike the case of edge-state-induced magnetization, the moments of magnetic impurities embedded in GNRs are found to be particularly stable in the presence of edge disorder. Our results suggest that the magnetic properties of transition-metal-doped GNRs are far more robust than those with moments arising intrinsically due to edge geometry.
PUBLISHED
Keywords: graphene; Nanoscience & Materials